Al-Farabi’s doctrine of sociology of knowledge - Hamid Parsania; Ruhollah Rezvani (Islām va ̒ulūm-i ijtimā̒ī)
One of the perennial concerns of scholars in the humanities and social sciences has always been epistemology. They disagree about its approach and principles, though. In west, after the renaissance, capitalist economy and society oriented views have affected the discussions concerning epistemology. But, epistemology, according to Islamic principles and the views of Muslim scholars has found ontological and existential foundations. Muslim scholars, especially Al-Farabi, regarding their comprehensive approach toward epistemology, considered the origins of knowledge derived from and influenced by a variety of factors. Hence, the role of wisdom and the knowledge of the unseen elements found a special status in Al-Farabi's epistemology. Al-Farabi's epistemology has been based on the principle of ontology and has used intuition, reason and revelation. The importance of Al-Farabi's epistemology was in highlighting the role of reason, the unseen world and society. Factors influencing knowledge, in Al-Farabi's view, have included the unseen world, purposive approach, sociocultural factors, education, economic status, sociopolitical climate, psychological features, worldview, interpersonal interactions and individuals will.